THAI TOURISTS’ AWARNESS TOWARDS CLIMATE CHANGE ON HOLIDAY MAKING - Soontayatron, Somruthai (Journal of Sports Science and Health, 2019)
Purpose This study aimed to explore Thai tourists’ awareness towards climate change on their holiday making. Methods This study was a quantitative research adopting questionnaires as a main method of data collection. This research adopted a convenience sampling method by handing a questionnaire that was provided to 400 potential Thai tourists, aged between 18 to 55 years old. This was a survey research using the closed-end questionnaire as a research tool. The pilot test was taken place with 30 respondents in order to do the reliability test by using the analyst of Cornbach’s Alpha Coefficient (0.93).The statistical data analysis in this study used frequency, percentage, mean, standard deviation and t-test with the statistical significance at 0.05. Results Most of the respondents were females, aged between 25 to 34, had children in their household, working full-time, and graduated from higher education. Most of them have ever taken oversea holidays and using car as their mode of transportation. The respondents, overall, were aware ( = 3.79, S.D. = 0.51) that there were problems towards climate change. The hypothesis testing showed that the levels of Thai tourists’ awareness towards climate change on their holiday making were not affected by the difference in type of holiday taken between oversea and non-oversea. Conclusion There were no differences between oversea and non-oversea holiday taken of Thai tourists’ awareness towards climate change on their holiday making. The attitude and behaviour correlations were found when actual behaviours were assessed that when self-report measurement was used. The difference between awareness and non-awareness was a matter of the strength of the attitude held, not a contrast in fundamental values.